Precocene II, a Trichothecene Production Inhibitor, Binds to Voltage-Dependent Anion Channel and Increases the Superoxide Level in Mitochondria of Fusarium graminearum - Furukawa, Tomohiro (Public Library of Science, 2015)

(untitled) (PLoS One)
Precocene II, a constituent of essential oils, shows antijuvenile hormone activity in insects and inhibits trichothecene production in fungi. We investigated the molecular mechanism by which precocene II inhibits trichothecene production in Fusarium graminearum, the main causal agent of Fusarium head blight and trichothecene contamination in grains. Voltage-dependent anion channel (VDAC), a mitochondrial outer membrane protein, was identified as the precocene II-binding protein by an affinity magnetic bead method. Precocene II increased the superoxide level in mitochondria as well as the amount of oxidized mitochondrial proteins. Ascorbic acid, glutathione, and α-tocopherol promoted trichothecene production by the fungus. These antioxidants compensated for the inhibitory activity of precocene II on trichothecene production. These results suggest that the binding of precocene II to VDAC may cause high superoxide levels in mitochondria, which leads to stopping of trichothecene production.